Dereplication-guided isolation of depsides thielavins S–T and lecanorins D–F from the endophytic fungus Setophoma sp. (March 2015) - de Medeiros, Lívia S.; Abreu, Lucas M.; Nielsen, Anita; Ingmer, Hanne; Larsen, Thomas O.; Nielsen, Kristian F.; Rodrigues-Filho, Edson
Graphical abstract: Depsides (1 –7 ) were isolated from Setophoma sp., a fungus isolated from symptomless guava fruits. Their detection was assisted by HRMS based-dereplication. Their polyketide structures (e.g.1, 4 and5 b ) were elucidated by means of HRMS/MS and NMR data analyses. Some compounds showed moderate activity against S. aureus . Highlights: Seven previously undescribed depsides were isolated from Setophoma sp. Their detection was assisted by UHPLC–HRMS based-dereplication. Depsides had no inhibitory effect on quorum sensing regulation activity of S. aureus. Some depsides showed moderate antibacterial activity against gram-positive bacteria. Abstract: Dereplication methodology using UHPLC–DAD–QTOFMS was applied during the metabolic profiling investigation of the endophyte Setophoma sp., a fungus isolated from symptomless guava fruits. The approach performed allowed a fast analysis of the microbial secondary metabolites. From this fungus, seven highly C-alkylated depsides were isolated and identified as polyketides thielavins S, T, U and V and lecanorins D, E and F. Their structures were elucidated through spectroscopic methods including NMR, HRMS and especially with assistance of HRMS/MS experiments. The compounds were tested for quorum sensing regulation activity in the virulence gene expression of Staphylococcus aureus, but no inhibitory effect was detected. Nevertheless, moderate antibacterial activity was encountered in three of tested depsides, particularly with thielavin T, whose MIC was 6.25 μg/mL against S. aureus .